Cultural values that influence the adaptation of girls who are refugees from sub-Saharan Africa living in the United States - Jessica Woodford; Savannah Krantz; Katherine Rial; Josephine Kalondji; Bernadette Musekura; Alexander Laywell; Sunita M. Stewart (Elsevier, 2023)
Literature suggests that discrepant family and host culture values complicate the acculturation and integration of immigrant youths. This qualitative study examines the adaptation experience of girls who are refugees from sub-Saharan Africa, a region where cultures are patriarchal and sex-based inequities are large, after resettlement in urban southwest United States, a more gender-equitable host environment. From July 2019 to August 2020, 44 semi-structured individual interviews were conducted with youths, parents, and cultural experts. We utilized the lens of the Integrated Resilience Model which combines resilience, acculturation, and developmental perspectives in understanding cultural adaptation in immigrant youths. We found that traditional tasks, attitudes, and expectations attached primarily to females and persisting in the host context include: the limited voice of women, the view that childhood for girls is preparation for marriage, and the custom of bride price. The dynamics of bride price drive parenting strategies that limit the exposure of girls to the host culture. Education is not traditionally typical for girls but is increasingly valued, benefitting the girl, family and local ethnocultural community. Parents' (particularly fathers') willingness to adopt gender-equitable attitudes towards education promotes the empowerment of girls. However, parents do not broadly support girls' autonomy, and girls stay closely connected to their cultural identity through many traditional beliefs and practices. Ethnic communities in the host setting influence and control their members. Pioneer families who promote education for their daughters also influence community opinion easing the path for girls who follow. Our study illustrates the nuanced process of cultural adaptation for these young women. With some repositioning on the part of the community, girls can thrive without severing essential ties to home and community.